Behavioral trading strategies and investor sentiment: Empirical research in Tehran stock exchange (TSE) - Mehrani, Kiarash; Roodposhti, Fereydoon Rahnamay; Nekomaram, Hashem; Saeedi, Ali (The Indonesian Capital Market Review, 2016)
In this study, we analyze contrarian and momentum strategies in periods associated with optimism or pessimism, and we compare them to the normal market sentiment condition. We evaluate the sentiment using the Arms adjusted index. Then, using the vector autoregressive test, we analyze the relationships among sentiment, stock returns, excess returns, and volatility. The results show that the formation of a short-term portfolio in one- and three-month periods of optimism and pessimism do not create additional returns and results in losses. In addition, the outcomes indicate that combining normal market sentiment with behavioral finance strategies increases performances, with more significant results seen using contrarian strategies compared to momentum strategies.